Techno-Economic Viability Assessment of Standalone Solar PV System for Rural Electric Power Supply - I.F. Ikechukwu; P. Chibueze (Journal of Applied Sciences and Environmental Management, 2022)
The techno-economic analysis emphasizing on energy production and cost of energy from photovoltaic stand-alone system at Umudike in eastern Nigeria was analyzed in this paper. This was carried out by obtaining data on the daily energy consumption of umudike, excess electricity and unmet electric load. The annual average solar irradiation considered in this study was obtained as 4.71kWh/m2/day. Hybrid Optimization of Multiple Energy Resources software was used to perform the technical and economic analysis of the stand-alone system in Umudike to ensure generation of uninterrupted power supply and to meet its energy demands, a photovoltaic system of 78.2 kW should be installed at a net present cost of $442,683 and an initial capital cost of $330,211. The photovoltaic stand-alone system will help to proffer solution to the daily power outages lasting several hours in Umudike. The photovoltaic Standalone System is a good source of continuous power generation, as it reduces combustion of fossil fuels and the consequent carbon dioxide emission which is the main cause of greenhouse-effect and global warming.